N-alkane profile in some plants grazed by sheep in Chilo Archipelago, Chile - Martnez Pelez, Mara Eugenia; Cesa, Ariela (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
In this study, the pattern of n-alkanes of fifteen species collected in a naturalized grassland grazed by sheep in the Archipelago of Chilo, Chile was analyzed. The concentrations of odd-chain n-alkanes between C23 and C31 were placed on the recommended values for obtaining reliable estimates of consumption. It was also observed that species showed marked differences in their individual patterns. The results show a promising horizon to advance in determining the composition of the diet of sheep grazing in the Archipelago of Chilo (Chile).